Реактивные изменения капиллярного кровотока в пульпе зубов при кариесе дентина и развитии пульпита (LLC "Endo Press", 2020)
Laser doppler flowmetry of a teeth intact, with dentine caries, an initial pulpitis and an acute focal pulpitis has been spent at 102 patients and has been established, that in comparison with a condition of a capillary blood flow in a teeth with dentine caries its level at an initial pulpitis increases in 2 times. At an acute focal pulpitis occurs sharp and essential (more than in 3 times) reduction of a capillary blood flow in comparison with its size at an initial pulpitis that can serve as differentsialnodiagnostic criterion of diseases of a pulp of a tooth.